LITERATURE STUDY OF FACTORS AFFECTING EMPLOYEE TURNOVER INTENTIONS IN INDONESIA - Dwi Wahyuni; Khairul Ikhwan (Transpublika Publisher, 2022)
Turnover intention is a human resource problem that is often faced by company in Indonesia, therefore researchers are encouraged to conduct research on turnover intention where the research method used is qualitative analysis with Charting the flied. The sample used is an article that discusses the turnover intention in 2016-2021 which includes 16 articles. The article can be accessed through the journal of Sinta 6. The data is classified based on the year of publication, independent variables, research methods, and important findings. The results of this study are that turnover intention is influenced by job satisfaction, organizational commitment, job stress, work and compensation.